On Optimal Trajectory in Space Flight - Orlov, S. (International Journal of Scientific Research in Civil Engineering, 2018)
Are investigated a trajectory of new type in distant, space flights unlike usual trajectories of direct flight to heavenly object (Moon) it is supposed to use asymmetry of a gravitational field and to carry out flight bypassing the most power gravitational impact on the spacecraft. It leads to economy of power for 20-30 %.
Keywords: The Theory of Vortex Gravitation; Space Flights With an Optimum Trajectory